Monoclonal antibodies to Mycoplasma hyorhinis surface antigens: tools for analyzing mycoplasma-lymphoid cell interactions. - Wise, K. S. (Yale Journal of Biology and Medicine, 1983)
A library has been constructed of approximately 50 monoclonal antibodies that recognize antigens of Mycoplasma hyorhinis. Characteristics of six antibodies are discussed. Each reacts with a discrete determinant borne on a protein-containing molecule of distinct molecular size. Three of these respective antigens are expressed at the surface of mycoplasmas colonizing lymphoblastoid cells in culture. Of these three surface antigens, two are selectively expressed on strain GDL but not on strain BTS-7 of M. hyorhinis, thus defining strain-restricted immunological specificities within these species. One monoclonal antibody of the IgM class (mu, kappa) mediated marked complement-dependent growth inhibition of M. hyorhinis in broth culture. These monoclonal reagents should facilitate analysis of mycoplasma surface architecture, and the molecular interactions of these organisms with the host cell surface.